2022
DOI: 10.1002/alz.12547
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of motoric cognitive risk—Hypotheses based on a systematic review and meta‐analysis of longitudinal cohort studies of older adults

Abstract: We aimed to refine the hypothesis that motoric cognitive risk (MCR), a syndrome combining measured slow gait speed and self-reported cognitive complaints, is prognostic of incident dementia and other major causes of morbidity in older age. We propose mechanisms on the relationship between motor and cognitive function and describe a roadmap to validate these hypotheses. We systematically searched major electronic databases from inception to August 2021 for original longitudinal cohort studies of adults aged ≥60… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 58 publications
6
32
0
5
Order By: Relevance
“…Our findings also revealed that the association between both items (i.e., inability to name the date and use of a walking aid and/or history of falls) and incident MNCD was significant and greater when combined, compared to the inability to name the date by itself. Again, this result is consistent with previous results reported on MCR [ 9 , 10 ]. Indeed, we report that the magnitude of this risk is two-fold when compared to the cognitive impairment item alone.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings also revealed that the association between both items (i.e., inability to name the date and use of a walking aid and/or history of falls) and incident MNCD was significant and greater when combined, compared to the inability to name the date by itself. Again, this result is consistent with previous results reported on MCR [ 9 , 10 ]. Indeed, we report that the magnitude of this risk is two-fold when compared to the cognitive impairment item alone.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, selected participants were free of MNCD at baseline and only those with temporal impairment had significant risk of incident MNCD. Although specific motor impairment related to gait disorders or mild parkinsonian signs may predict cognitive decline, the association between cognitive impairment and incident MNCD is stronger than between motor impairment and incident MNCD [ 7 , 8 , 9 ]. Finally, there are more mixed results regarding the association between motor impairment and incident MNCD compared to cognitive impairment [ 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2022 systematic review and meta-analysis found that, compared to those without MCR, those with MCR are at over twice the risk of developing dementia after 4.3 years of follow-up and 76% more likely to develop cognitive impairment after 5.6 years of follow up. 7 MCR is also prognostic of future falls and earlier mortality. 7…”
Section: Introductionmentioning
confidence: 99%